Health Insurance Reform and HMO Penetration in the Small Group Market - Thomas C. Buchmueller; Su Liu (SAGE Publishing, 2005)
This study uses data from several national employer surveys conducted between the late 1980s and the mid-1990s to investigate the effect of state-level underwriting reforms on HMO penetration in the small group health insurance market. We identify reform effects by exploiting cross-state variation in the timing and content of reform legislation and by using mid-sized and large employers, which were not affected by the legislation, as within-state control groups. While it is difficult to disentangle the effect of state reforms from other factors affecting HMO penetration in the small group markets, the results suggest a positive relationship between insurance market regulations and HMO penetration.